2002
DOI: 10.1073/pnas.102179399
|View full text |Cite
|
Sign up to set email alerts
|

Position-effect protection and enhancer blocking by the chicken β-globin insulator are separable activities

Abstract: The 1.2-kb DNA sequence element (5HS4) at the 5 end of the chicken ␤-globin locus has the two defining properties of an insulator: it prevents an ''external'' enhancer from acting on a promoter when placed between them (''enhancer blocking'') and acts as a barrier to chromosomal position effect (CPE) when it surrounds a stably integrated reporter. We previously reported that a single CTCF-binding site in 5HS4 is necessary and sufficient for enhancer blocking. We show here that a 250-bp ''core'' element from wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
333
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(363 citation statements)
references
References 32 publications
22
333
2
1
Order By: Relevance
“…However, wellknown insulator-binding protein CTCF is not a likely candidate since this protein is reported to be strongly associated with enhancer-blocking activity, rather than anti-silencing effect in studies using cHS4. 18 One can also attribute the cell type selectivity to the physiological role of insulators, that is, the regulation of stage-specific gene expression by regulating higher chromatin structure. 16,17 Recently, double-stranded DNA-binding protein, SATB1, was reported to play a key role in forming thymocytespecific nuclear architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, wellknown insulator-binding protein CTCF is not a likely candidate since this protein is reported to be strongly associated with enhancer-blocking activity, rather than anti-silencing effect in studies using cHS4. 18 One can also attribute the cell type selectivity to the physiological role of insulators, that is, the regulation of stage-specific gene expression by regulating higher chromatin structure. 16,17 Recently, double-stranded DNA-binding protein, SATB1, was reported to play a key role in forming thymocytespecific nuclear architecture.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,[15][16][17][18][19] Previous reports have shown that HS4 insulator protects transgenes from position effect variegation when introduced into MoMLV-based retroviral vectors. 20,21 Since the HS4 fragment is active in restricted cell types, 21 a quest for alternative insulators is necessary to propagate the use of the insulator in various cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The gateway cassette (Invitrogen, Cassette B from Gateway Vector Conversion System) was cloned in blunt into the KpnI restriction site generating the insulator vector pminiTol2-Z48-Gw-CARGFP. Two copies of the ␤-globin 5Ј HS4 250-pb insulator (Recillas-Targa et al, 2002), previously cloned in pBluescript, were amplified with the T3 and T7 primers. The PCR fragment was cloned in TOPO vector (Invitrogen, pCR®8/GW/TOPO® TA cloning KIT) and transferred to the insulator test vector by in vitro recombination (Invitrogen, Gateway LR clonase II Enzyme mix).…”
Section: Insulator Vectorsmentioning
confidence: 99%
“…Third, the enhancer reporter cassette in ZED is flanked by insulator sequences that we show decrease position effects, thereby increasing the specificity of the signal. We have used two different insulators, the 5ЈHS4 insulator from the chicken beta-globin gene (Chung et al, 1993;Recillas-Targa et al, 2002) and the GAB insulator element from the mouse tyrosinase gene (Montoliu et al, 1996), which we show here to maintain their insulator function in zebrafish. Also, ZED contains a cardiac actin promoter driving the expression of a red fluorescent protein (DsRed) that serves as control for transgenesis efficiency in vivo in the F0 and the F1 embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of the FVIII-HAC using CHO cells A single copy of the FVIII expression cassette was 9.1 kb and composed of the following DNA elements: the HS4 insulator sequences derived from pCJ5-4 (gifted by Dr G Felsenfeld), 11,12 the cytomegalovirus immediate early enhancer-chicken b-actin hybrid promoter 13 (gifted by Dr M Okabe), a human B-domain deleted factor VIII (FVIII) 14 and a bovine growth hormone poly A signal. FVIII-expression cassettes (1 to 16 copies) were inserted into the modified pPAC4 vector (see Supplementary Figure 1).…”
mentioning
confidence: 99%